Fungal sepsis in a Level III Neonatal Intensive Care Unit: a 10-year retrospective analysis - Rita Silva; Marta Grilo; Susana Pissarra; Hercília Guimarães (Hygeia Press di Corridori Marinella, 2014)
Objective: Neonatal sepsis caused by fungal agents entails great mortality and morbidity. The goals of this study are to characterize local epidemiology, to analyze the presence of risk factors, laboratorial findings, and to describe therapeutics performed and their effectiveness. Method: In a retrospective study performed at the neonatal intensive care unit of "Centro Hospitalar São João", Porto, Portugal, patients who had positive blood cultures for fungus between 2003 and 2012 were selected. Results: From a total population of 3,933 patients, 15 (3.8 in every 1,000) had sepsis caused by fungal agents. Eleven (73.3%) patients were very-preterm and 9 (60%) were extremely low birth weight. All patients had central venous catheters, received parenteral nutrition and broad-spectrum antibiotics, and most were invasively ventilated (n = 14, 86.7%). Candida spp., namely C. albicans (n = 7, 43.8%) and C. parapsilosis (n = 9, 56.3%), were the identified agents. Patients were treated with liposomal amphotericin B alone (n = 9, 60%) or with the addition or replacement of flucytosine, caspofungin, or fluconazole. First choice treatment was effective in 7 patients (46.7%). Mortality occurred in 46.7% (n = 7). Conclusions: Although the incidence of fungal sepsis was in accordance with what is described in the literature, mortality was higher. Rates of C. albicans and C. parapsilosis were also similar to other reports. Well-known modifiable risk factors for fungal sepsis could be identified in most cases. These data must be considered in the prevention of fungal sepsis in neonatal intensive care units.